Mechanisms of muscle insulin resistance and the cross‐talk with liver and adipose tissue - Silva Rosa, Simone C.; Nayak, Nichole; Caymo, Andrei Miguel; Gordon, Joseph W. (Physiological reports, 2020)
Insulin resistance is a metabolic disorder affecting multiple tissues and is a precursor event to type 2 diabetes (T2D). As T2D affects over 425 million people globally, there is an imperative need for research into insulin resistance to better understand the underlying mechanisms. The proposed mechanisms involved in insulin resistance include both whole body aspects, such as inflammation and metabolic inflexibility; as well as cellular phenomena, such as lipotoxicity, ER stress, and mitochondrial dysfunction. Despite numerous studies emphasizing the role of lipotoxicity in the pathogenesis of insulin resistance, an understanding of the interplay between tissues and these proposed mechanisms is still emerging. Furthermore, the tissue‐specific and unique responses each of the three major insulin target tissues and how each interconnect to regulate the whole body insulin response has become a new priority in metabolic research. With an emphasis on skeletal muscle, this mini‐review highlights key similarities and differences in insulin signaling and resistance between different target‐tissues, and presents the latest findings related to how these tissues communicate to control whole body metabolism. Overview of insulin resistance mechanisms: the ability of the mitochondria to respond to metabolic disruptions is essential for healthy cellular bioenergetics, and interference with this process may prompt unregulated mitochondrial biogenesis and mitophagy, thus contributing to insulin resistance in major insulin target tissues.